2021
DOI: 10.1111/os.13044
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐Assisted Minimally Invasive Transforaminal Lumbar Interbody Fusion in the Treatment of Lumbar Spondylolisthesis

Abstract: Objective: To compare the clinical efficacy between robot-assisted minimally invasive transforaminal lumbar interbody fusion (robot-assisted MIS-TLIF) and traditional open TLIF surgery in the treatment of lumbar spondylolisthesis.Methods: According to the inclusion and exclusion criteria, 48 cases with lumbar spondylolisthesis who received surgical treatment from June 2016 to December 2017 in the spinal surgery department of Beijing Jishuitan Hospital were analyzed in this study, including 23 patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 24 publications
1
50
2
Order By: Relevance
“…Robot-assisted pedicle screw placement has become popular in recent years, and it has been proven to have greater screw accuracy [ 2 , 3 , 4 , 5 ], fewer proximal facet joint violations [ 2 , 6 ], and reduced radiation exposure [ 2 , 5 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robot-assisted pedicle screw placement has become popular in recent years, and it has been proven to have greater screw accuracy [ 2 , 3 , 4 , 5 ], fewer proximal facet joint violations [ 2 , 6 ], and reduced radiation exposure [ 2 , 5 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, robotic systems have been developed to assist pedicle screw placement in spinal surgery. According to previous literature, robot-assisted pedicle screw placement has greater screw accuracy [ 2 , 3 , 4 , 5 ], fewer proximal facet joint violations [ 2 , 6 ], reduced radiation exposure [ 2 , 5 , 7 , 8 ], and shorter length of hospital stay [ 7 ]. However, only a few studies have compared the postoperative clinical and radiographic outcomes between robot-assisted pedicle screw placement and fluoroscopy-guided technique.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion cage is placed in the vertebral space. but the disadvantage of PLIF is that the nerve root and dural sac need to be pulled through the midline during the operation, which increases the risk of nerve root and dural sac injury, especially above the lumbar 3 segment (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of mobility of the dural sac and the limited traction space easily lead to nerve injury (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The experience of Cui et al [ 91 ] with robotic-assisted pedicle screw placement in 23 MIS-TLIF patients revealed significant favorability in pedicle screw accuracy, intraoperative blood loss, postoperative pain, postoperative drainage, recovery time, and paraspinal muscle atrophy relative to 25 open TLIF patients. Lin et al [ 92 ] compared 75 MIS-TLIF patients who underwent robotic-assisted pedicle screw fixation to 149 patients receiving freehand fluoroscopy-assisted fixation, noting similar postoperative outcomes between cohorts, with robotic-assisted patients experiencing significantly reduced blood loss, as well as reduced operative time for procedures on more than 3 vertebral levels.…”
Section: Looking Ahead: Continued Evolution Of the Mis-tlifmentioning
confidence: 99%